Postcopulatory cost of immune system activation in Poecilia reticulata. Issue 3 (4th May 2017) - Devigili, Alessandro; Belluomo, Vincenzo; Locatello, Lisa; Rasotto, Maria B.; Pilastro, Andrea
Abstract : The function and maintenance of the immune system impose costs that can take the form of energy consumption and/or physiological side effects. These, in turn, can affect the expression of several traits, including traits closely related to fitness. The interaction of the immune system with other life-history traits (e.g. growth and survival) and with precopulatory sexually selected traits (e.g. male ornaments) has been widely studied, whereas little is known about its interplay with postcopulatory sexually selected traits, such as sperm characteristics. We studied the effects of an immune challenge on the expression of precopulatory and postcopulatory traits in the guppy, Poecilia reticulata . We injected two groups of males with a lipopolysaccharide (LPS) solution or a saline solution (control) and compared the effects of the immune system activation on traits' expression. The results showed a specific negative effect of the LPS injection on sperm traits, whereas precopulatory ornaments were lowered merely by manipulation (injection). We discuss the possible mechanisms underlying our findings, and the evolutionary implications that follow.